2021
DOI: 10.1371/journal.pcbi.1009054
|View full text |Cite
|
Sign up to set email alerts
|

A physicochemical model of odor sampling

Abstract: We present a general physicochemical sampling model for olfaction, based on established pharmacological laws, in which arbitrary combinations of odorant ligands and receptors can be generated and their individual and collective effects on odor representations and olfactory performance measured. Individual odor ligands exhibit receptor-specific affinities and efficacies; that is, they may bind strongly or weakly to a given receptor, and can act as strong agonists, weak agonists, partial agonists, or antagonists… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 95 publications
(187 reference statements)
0
5
0
Order By: Relevance
“…Concentration increases, however, generally evoke monotonic increases in the activation levels of individual glomeruli (and also may progressively recruit some new, lower-affinity glomeruli). These increases will not be linearly proportional to one another across glomeruli, but to a substantial extent the ordinal ranking of glomerular activation levels should be preserved (Araneda, Kini, & Firestein, 2000; Gronowitz et al, 2021). Quality differences, in contrast, involve sharply different ordinal rankings of glomerular activation levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration increases, however, generally evoke monotonic increases in the activation levels of individual glomeruli (and also may progressively recruit some new, lower-affinity glomeruli). These increases will not be linearly proportional to one another across glomeruli, but to a substantial extent the ordinal ranking of glomerular activation levels should be preserved (Araneda, Kini, & Firestein, 2000; Gronowitz et al, 2021). Quality differences, in contrast, involve sharply different ordinal rankings of glomerular activation levels.…”
Section: Methodsmentioning
confidence: 99%
“…These limitations on our understanding persist in part because odorant stimuli are difficult to control. All odorants – even monomolecular odorants – bind to multiple types of primary odorant receptors with different affinities and efficacies (discussed in Gronowitz, Liu, Qiu, Yu, & Cleland, 2021), such that primary olfactory sensory neuron (OSN) activation profiles vary nonlinearly and sometimes non-monotonically with concentration. Moreover, the timing of odor stimulus delivery is imprecise, rendering it difficult to determine whether variations in fine-scale temporal response properties arise from internally regulated OB network dynamics or simply from the undercontrolled timing of odorant delivery to receptors.…”
Section: Introductionmentioning
confidence: 99%
“…that divergent innervation of multiple glomeruli by the same type of axons did not compromise odor detection, discrimination, or associative learning (Qiu, Wu, Ma, Xu, et al, 2021). Discrimination is only affected under extremely challenging conditions, for example, with highly similar odor mixtures (Gronowitz et al, 2021). However, response to innately recognized odors is altered in these mice (Qiu, Wu, Ma, Xu, et al, 2021).…”
Section: Cellular and Molecular Mechanisms Underlying Plasticity Duri...mentioning
confidence: 98%
“…In one study, by leveraging the requirement of spontaneous activity in establishing the convergent axon innervation pattern, Qiu and colleagues used inducible expression of Kir2.1 to perturb the olfactory map and showed that divergent innervation of multiple glomeruli by the same type of axons did not compromise odor detection, discrimination, or associative learning (Qiu, Wu, Ma, Xu, et al, 2021). Discrimination is only affected under extremely challenging conditions, for example, with highly similar odor mixtures (Gronowitz et al, 2021). However, response to innately recognized odors is altered in these mice (Qiu, Wu, Ma, Xu, et al, 2021).…”
Section: The Critical Period Of Olfactory System Developmentmentioning
confidence: 99%
“…The anatomical arrangement in the AOB has strong implications as to how species-specific cues are encoded and how the information is processed. In the MOB, when the convergent glomerular innervation is experimentally perturbed to become divergent, it does not affect detection or discrimination of odorants but diminishes behavioral responses to innately recognized odors 74,75 . Thus, stereotypic projection patterns provide a basis for genetically specified connections in the neural circuitry to enable innate behaviors.…”
Section: Introductionmentioning
confidence: 99%